(untitled) (International conference on multidisciplinary science, 2025)
Chronic obstructive pulmonary disease (COPD) and allergic bronchitis are among the most common inflammatory diseases of the lungs, with external environmental factors (smoking, harmful industrial dust, atmospheric pollution) and immuno-allergic mechanisms playing a key role in their development. Clinically, both diseases manifest with shortness of breath, cough, and sputum production. In terms of pathogenetic mechanisms, irreversible fibrotic changes of the bronchial walls and bronchospasm are predominant in COPD, whereas in allergic bronchitis, IgE-mediated sensitization, degranulation of cells involved in the allergic reaction, and disturbance of cytokine balance play the main role.